Progressive Multifocal Leukoencephalopathy in a Multiple Sclerosis Patient Diagnosed after Switching from Natalizumab to Fingolimod - Tim Sinnecker; Jalal Othman; Marc Kühl; Imke Metz; Thoralf Niendorf; Annett Kunkel; Friedemann Paul; Jens Wuerfel; Juergen Faiss (Case Reports in Neurological Medicine)
Background. Natalizumab- (NTZ-) associated progressive multifocal leukoencephalopathy (PML) is a severe and often disabling infectious central nervous system disease that can become evident in multiple sclerosis (MS) patients after NTZ discontinuation. Recently, novel diagnostic biomarkers for the assessment of PML risk in NTZ treated MS patients such as the anti-JC virus antibody index have been reported, and the clinical relevance of milky-way lesions detectable by MRI has been discussed. Case Presentation and Conclusion. We report a MS patient in whom PML was highly suspected solely based on MRI findings after switching from NTZ to fingolimod despite repeatedly negative (ultrasensitive) polymerase chain reaction (PCR) testing for JC virus DNA in cerebrospinal fluid. The PML diagnosis was histopathologically confirmed by brain biopsy. The occurrence of an immune reconstitution inflammatory syndrome (IRIS) during fingolimod therapy, elevated measures of JCV antibody indices, and the relevance of milky-way-like lesions detectable by (7 T) MRI are discussed.